Should EU cross-border cooperation programmes focus mainly on reducing border obstacles? - Medeiros, E. (2018)
EU cross-border cooperation programmes were formally established with the launching of the first INTERREG Community Initiative (1989-1993). Since then, these programmes have been expanding to Northern and Eastern Europe. At present, the INTERREG V-A (2014-2020), formally known as European Territorial Cooperation (strand A – crossborder cooperation), covers more than 60% of the EU territory and 40% of EU inhabitants, making it one of the most politically relevant EU financed programmes. For the most part, however, these programmes are still regarded by both the European Commission and national and regional authorities as a complementary financial tool to support growth and regional development strategies. In this context, this article analyses what have been the main strategic goals of the EU cross-border cooperation programmes, whilst supporting a new strategic paradigm for these programmes during the post-2020 EU policies programming phase focused on reducing the barrier-effects in all their main dimension